2017
DOI: 10.1073/pnas.1707965114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tumor-promoter cholesterol metabolite in human breast cancers acting through the glucocorticoid receptor

Abstract: Breast cancer (BC) remains the primary cause of death from cancer among women worldwide. Cholesterol-5,6-epoxide (5,6-EC) metabolism is deregulated in BC but the molecular origin of this is unknown. Here, we have identified an oncometabolism downstream of 5,6-EC that promotes BC progression independently of estrogen receptor α expression. We show that cholesterol epoxide hydrolase (ChEH) metabolizes 5,6-EC into cholestane-3β,5α,6β-triol, which is transformed into the oncometabolite 6-oxo-cholestan-3β,5α-diol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 51 publications
6
110
0
Order By: Relevance
“…Patient breast cancer samples showed significant increase in OCDO levels and greater ChEH and 11bHSD2 protein expression compared with normal tissues (15). The analysis of several human breast cancer mRNA databases indicated that 11bHSD2 and ChEH subunit overexpression was correlated with a higher risk of patient death in breast cancer and that high GR expression or activation was correlated with poor therapeutic response or prognosis in many solid tumors including breast cancer (15). Interestingly, ChEH inhibition and 11bHSD2 silencing inhibited OCDO production and tumor growth and mifepristone, a GR antagonist, as well as GR silencing inhibits OCDO-induced tumor cell proliferation (15).…”
Section: Oxysterols As Oncopromoter Metabolites Targeting Nuclear Recmentioning
confidence: 94%
See 3 more Smart Citations
“…Patient breast cancer samples showed significant increase in OCDO levels and greater ChEH and 11bHSD2 protein expression compared with normal tissues (15). The analysis of several human breast cancer mRNA databases indicated that 11bHSD2 and ChEH subunit overexpression was correlated with a higher risk of patient death in breast cancer and that high GR expression or activation was correlated with poor therapeutic response or prognosis in many solid tumors including breast cancer (15). Interestingly, ChEH inhibition and 11bHSD2 silencing inhibited OCDO production and tumor growth and mifepristone, a GR antagonist, as well as GR silencing inhibits OCDO-induced tumor cell proliferation (15).…”
Section: Oxysterols As Oncopromoter Metabolites Targeting Nuclear Recmentioning
confidence: 94%
“…Interestingly, an oncometabolism downstream of 5,6a-EC and 5,6b-EC (5,6EC) was identified in breast cancer in human and animal models (15). The cholesterol epoxide hydrolase (ChEH), formed by the D8D7I and 3b-hydroxysterol-D 7 -reductase (DHCR7) enzymes, is known to metabolize 5,6-ECs into cholestane-3b,5a,6b-triol (CT) in normal tissues (4,16).…”
Section: Oxysterols As Oncopromoter Metabolites Targeting Nuclear Recmentioning
confidence: 99%
See 2 more Smart Citations
“…In cancer, they have been demonstrated to play an important role in the regulation of cancer progression. Their functions include the regulation of cellular signaling pathways involved in cell cycle regulation as well as other pathways regulating cancer cell migration and survival [5][6][7]. In several types of cancer, plasma cholesterol levels have been shown to regulate tumor formation and cancer aggressiveness [8,9].…”
Section: Introductionmentioning
confidence: 99%